Nasturtium, Garden—Tropaeolum majus L. - James M. Stephens (EDIS)
This document provides an overview of the garden nasturtium (Tropaeolum majus), a flowering plant commonly grown in Florida for both ornamental and edible purposes. It describes the plant’s characteristics, including its edible leaves, flowers, and seed pods, and outlines its cultivation requirements. The document also distinguishes between the tall and dwarf varieties and offers guidance on planting, care, and harvesting. Original publication date May 1994.